Empowering Youth Through the Power of Reflective Journaling: Understanding Life Skills from the Reflections of Youth - Dawn Anderson-Butcher; Tarkington J Newman; Ellen Williams (Youth)
Youth sport research has routinely suggested that sport has the potential to serve as a meaningful context for learning. particularly when programs are designed to promote positive youth development (PYD) outcomes. Indeed, participation in sport-based PYD programs has been shown to lead to the development and transfer of life skills. Yet, even given the growth of sport-based PYD research over the last two decades, much remains unknown about specific programmatic design features. Promising practices point to the role of reflection in facilitating life skill development and the application of newly learned skills to real-life. This study investigates the reflective journaling of 234 youth experiencing social vulnerabilities who participated in a sport-based PYD program called LiFEsports. Thematic analyses explored text and illustrations included in youth journals. Results suggest that youth both understand and consider how life skills (i.e., self-control, effort, teamwork, social responsibility, personal responsibility, leadership) can be transferred to settings such as at home, during school and in the community. Further findings highlight the relationship between significant others (e.g., teammates, coaches, parents) and life skills transfer, particularly related to reinforcement. Ultimately, journaling may serve as a viable method to prompt reflections among youth.